2019
DOI: 10.1002/cepa.1201
|View full text |Cite
|
Sign up to set email alerts
|

Damage Model Calibration for S275 and S690 Steels

Abstract: A calibration procedure for material damage models of S275 and S690 structural steels is proposed based on their full range engineering stress‐strain curves. Combined linear and power stress‐strain laws with a weighting factor are used to describe damaged stress‐strain relations after necking. Material damage models are proposed based on the estimation of undamaged stress. Tensile coupon tests on S275 and S690 steels are modelled in ABAQUS with the explicit solver. Results show that the numerical engineering s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Therefore, the range of validity for the weighting factor W in Equation (3) was defined in the range between 0 and 1. However, in the recent study on the post-necking true stress of high-strength steels, it was found that using the power low of Equation ( 5) would overestimate the post-necking stress [33,34]. Therefore, the power law should not be subjectively considered as the lower bound to describe the post-necking true stress.…”
Section: Full-range True Stress-strain Relationsmentioning
confidence: 99%
“…Therefore, the range of validity for the weighting factor W in Equation (3) was defined in the range between 0 and 1. However, in the recent study on the post-necking true stress of high-strength steels, it was found that using the power low of Equation ( 5) would overestimate the post-necking stress [33,34]. Therefore, the power law should not be subjectively considered as the lower bound to describe the post-necking true stress.…”
Section: Full-range True Stress-strain Relationsmentioning
confidence: 99%
“…( 16). Yang and Veljkovic [17,18] extended the combined linear and power stress-strain law to describe the post-necking stress-strain relationships of high-strength steels with weighting factor less than zero:…”
Section: Tablementioning
confidence: 99%
“…Full-range true stress-strain curves for high-strength steels have been investigated in [30,31]. The pre-necking true stress-strain can be obtained by converting equations between engineering stress-strain and true stress-strain, as shown in Eqs.…”
Section: Materials Behavioursmentioning
confidence: 99%